Sustainability Development and Organizational Performance in a Developing Economy: Evidence from Malaysia - Hashim Al-Saedi, Sami; Abdullah Abbas, Yasir (South Asian Journal of Social Sciences and Humanities, 2023)
The purpose of this paper is to determine the impact of the sustainability development (SD) on the organizational performance (OP) of Bursa Malaysia as a developing economy. This paper used secondary data obtained from the content analysis of annual reports and Datastream of 140 samples listed on Bursa Malaysia for the period of 2008-2018 and used the WLS and OLS regressions. The results show that there is a positive relationship among SD and its determinants (energy, general public, product, and employee) with OP. To the knowledge of the reviewers, this paper has a significant impact in terms of SD in organizations in Bursa Malaysia.